Design and Implementation of Automatic Auxiliary Alignment System for Train Based on BeiDou Positioning - WU Yue; XIAO Lizhi; WU Xiaoxin (Kongzhi Yu Xinxi Jishu, 2023)
In the field of operation safety control of railway trains, the driving alignment is considered as the reference point for the basic data of the train operation monitoring device (LKJ). At present, trains depart usually after visual check against the preset alignment reference, which is subject to environmental constraints and defects from manual operation such as uncontrollable alignment error. In order to accurately identify the stock track, route and kilometer mark of the train, and realize the precise operation control of the train, this paper proposes an automatic auxiliary alignment design of train based on the high-precision BeiDou positioning technology, which enables automatic setting of initial station parameters and automatic auxiliary driving alignment for train operation by combining the real-time dynamic BeiDou positioning technology and high-precision onboard station/yard map data. The field application results show that after adopting this system,the positioning accuracy of BeiDou reaches 2 cm, the control accuracy of automatic driving alignment is within 1 m, and the success rate of accurate automatic auxiliary alignment is 99.9% under the condition of high confidence, which indicates the proposed design can effectively prevent the safety risks lying in manual alignment, reduce the labor intensity of train drivers and improve the operational efficiency of railroad transport enterprises.